1995
DOI: 10.1063/1.114745
|View full text |Cite
|
Sign up to set email alerts
|

Large electromagnetic stop bands in metallodielectric photonic crystals

Abstract: An electromagnetic stop band spanning about one octave is observed in a periodic structure consisting of a face-centered-cubic Bravais lattice of metal spheres supported by a low-loss dielectric. The low-frequency edge of the stop band is consistent with the Mie condition for the metallic spheres, and the center frequency of the stop band is a function of the lattice constant and the support dielectric material. For example, a sample having a cubic lattice constant of 1.65 cm, 3/8 in. diam chrome spheres at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 0 publications
2
70
0
Order By: Relevance
“…Brown and McMahon [9] have fabricated metallodielectric PBG material with metal spheres arranged in a fcc lattice, and observed stop bands in the microwave regime. Fan et al [6] showed that the experimentally observed stop band is the result of a directional gap in the (111) direction, while a complete band gap can be realized by arranging the spheres in the diamond structure.…”
mentioning
confidence: 99%
“…Brown and McMahon [9] have fabricated metallodielectric PBG material with metal spheres arranged in a fcc lattice, and observed stop bands in the microwave regime. Fan et al [6] showed that the experimentally observed stop band is the result of a directional gap in the (111) direction, while a complete band gap can be realized by arranging the spheres in the diamond structure.…”
mentioning
confidence: 99%
“…It has been found that the inverse-opal technique and the glancing angle deposition (GLAD) method are suitable for microfabrication of three-dimensional PCs in the optical or infrared frequencies [10][11][12]. Recently, the introduction of a metal scattering centre with a small volume fraction as the composite material instead of pure dielectrics has allowed the construction of so-called metallodielectric photonic crystals (MDPCs) [13][14][15]. This class of composite 1 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, metallic photonic structures have some primary advantages over the correspondent with dielectrics: light weight, reduced size, lower cost, and fabrication versatility. 3,4 A more important feature lies in the photonic band gap, which extends from zero frequency up to the first band pass edge, meanwhile pure dielectric photonic structures exhibit a relatively narrow forbidden band gap. On the other hand, the performances of dielectric structures can be also obtained in metallic ones by adequately changing the design parameters, 3,4 for instance in applications as frequency selective surfaces ͑FSS͒.…”
Section: Introductionmentioning
confidence: 99%